How parenting styles affect primary school students’ subjective well-being? The mediating role of self-concept and emotional intelligence - Tiantian Gao; Baoqian Li; Shuxian Liang; Wanmeng Zhou; Xinyi Zhu; Lu Bai; Guoqiang Li (Frontiers in Psychology)
PurposeTo explore the relationship between parenting styles and self-concept, emotional intelligence, and subjective well-being among primary school students.MethodsIn total, 1,683 students from 10 primary schools in Hangzhou, China, were surveyed using a simple random sampling method. Participants completed the Parenting Style Scale, the Self-Concept Scale, the Emotional Intelligence Scale, and the Subjective Well-Being Scale.Results(1) Father’s and mother’s emotional warmth was significantly positively correlated with students’ subjective well-being (r = 0.513, p < 0.01 and r = 0.478, p < 0.01, respectively). Father’s and mother’s rejection was significantly negatively correlated with students’ subjective well-being (r = −0.257, p < 0.01 and r = −0.285, p < 0.01, respectively). Father’s overprotection was significantly negatively correlated with students’ subjective well-being (r = −0.178, p < 0.01; r = −0.227, p < 0.01). (2) Self-concept and emotional intelligence acted as chain mediators between father’s and mother’s emotional warmth and students’ subjective well-being (0.337, 0.477 and 0.366, 0.520, respectively). Self-concept and emotional intelligence acted as chain mediators between father’s and mother’s rejection and students’ subjective well-being (−0.590, −0.377 and −0.693, −0.460, respectively). Self-concept chain-mediated between father’s and mother’s overprotection and students’ subjective well-being (−0.380, −0.224 and −0.413, −0.264 respectively).ConclusionParenting styles can affect primary school student’s subjective well-being both directly and through mediating effects. Self-concept and emotional intelligence partially mediate the impact of emotional warmth and rejection parenting styles, and fully mediate the impact of father’s overprotective parenting on subjective well-being.